A new hypothesis for the pathophysiology of complex regional pain syndrome. (October 2018) - Russo, Marc; Georgius, Peter; Santarelli, Danielle M
Abstract: Complex Regional Pain Syndrome (CRPS) has defied a clear unified pathological explanation to date. Not surprisingly, treatments for the condition are limited in number, efficacy and their ability to enact a cure. Whilst many observations have been made of physiological abnormalities, how these explain the condition and who does and doesn't develop CRPS remains unclear. We propose a new overarching hypothesis to explain the condition that invokes four dynamically changing and interacting components of tissue trauma, pathological pain processing, autonomic dysfunction (both peripheral and central) and immune dysfunction, primarily involving excessive and pathological activation of dendritic cells following trauma or atrophy. We outline pathophysiological changes that may initiate a cascade of events involving dendritic cells and the cholinergic anti-inflammatory pathway resulting in the condition, and the changes that maintain the condition into its chronic phase. This hypothesis should provide fertile ground for further investigations and development of new treatments that holistically address the nature of the disorder along its developmental continuum.